Terrorism in Australia: factors associated with perceived threat and incident-critical behaviours - Raphael Beverley; Barr Margo; Taylor Melanie; Agho Kingsley; Stevens Garry; Jorm Louisa (BMC, 2009)
Abstract Background To help improve incident preparedness this study assessed socio-demographic and socio-economic predictors of perceived risk of terrorism within Australia and willingness to comply with public safety directives during such incidents. Methods The terrorism perception question module was incorporated into the New South Wales Population Health Survey and was completed by a representative sample of 2,081 respondents in early 2007. Responses were weighted against the New South Wales population. Results Multivariate analyses indicated that those with no formal educational qualifications were significantly more likely (OR = 2.10, 95%CI:1.32-3.35, p < 0.001) to think that a terrorist attack is very or extremely likely to occur in Australia and also more likely (OR = 3.62, 95%CI:2.25-5.83, p < 0.001) to be very or extremely concerned that they or a family member would be directly affected, compared to those with a university-level qualification. Speaking a language other than English at home predicted high concern (very/extremely) that self or family would be directly affected (OR = 3.02, 95%CI:2.02-4.53, p < 0.001) and was the strongest predictor of having made associated changes in living (OR = 3.27, 95%CI:2.17-4.93, p < 0.001). Being female predicted willingness to evacuate from public facilities. Speaking a language other than English at home predicted low willingness to evacuate. Conclusion Low education level is a risk factor for high terrorism risk perception and concerns regarding potential impacts. The pattern of concern and response among those of migrant background may reflect secondary social impacts associated with heightened community threat, rather than the direct threat of terrorism itself. These findings highlight the need for terrorism risk communication and related strategies to address the specific concerns of these sub-groups as a critical underpinning of population-level preparedness.